Finding San Carlino : collected perspectives on the geometry of the Baroque - Mansure, Adil; Luarasi, Skender (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"The church of San Carlo alle Quattro Fontane, also called San Carlino, is an architectural artefact that continues to attract numerous hypotheses and geometric analyses attempting to explain its form and meaning"--
OCLC-licensed vendor bibliographic record.
Keywords: Borromini, Francesco, -- 1599-1667 -- Criticism and interpretation; Chiesa di S. Carlo alle Quattro Fontane (Rome, Italy); Geometry in architecture; Symbolism in architecture -- Italy -- Rome; ARCHITECTURE / General; ARCHITECTURE / Design & Drafting